2020
DOI: 10.1002/advs.202002232
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Long Non‐Coding RNA lnc030 Maintains Breast Cancer Stem Cell Stemness by Stabilizing SQLE mRNA and Increasing Cholesterol Synthesis

Abstract: Cancer stem cells (CSCs) are considered the roots of cancer metastasis and recurrence (CSCs), due in part to their self‐renewal and therapy resistance properties. However, the underlying mechanisms for the regulation of CSC stemness are poorly understood. Recently, increasing evidence shows that long non‐coding RNAs (lncRNAs) are critical regulators for cancer cell function in various malignancies including breast cancer, but how lncRNAs regulate the function of breast cancer stem cells (BCSCs) remains to be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 55 publications
0
59
0
Order By: Relevance
“…These results suggested that DCBLD2 was potentially involved in the regulation of cell stemness and might serve as a promising therapeutic target for PDAC. Function analysis of DCBLD2 revealed that this gene was positively associated with several pathways participating in stemness regulation, such as PI3K-AKT signaling pathway ( Qin et al, 2021 ; Yoon et al, 2021 ) and Hippo signaling pathway ( Cordenonsi et al, 2011 ; Park et al, 2018 ). These findings could provide new insight into biological implications and clinical relevance of DCBLD2 in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that DCBLD2 was potentially involved in the regulation of cell stemness and might serve as a promising therapeutic target for PDAC. Function analysis of DCBLD2 revealed that this gene was positively associated with several pathways participating in stemness regulation, such as PI3K-AKT signaling pathway ( Qin et al, 2021 ; Yoon et al, 2021 ) and Hippo signaling pathway ( Cordenonsi et al, 2011 ; Park et al, 2018 ). These findings could provide new insight into biological implications and clinical relevance of DCBLD2 in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…ERK phosphorylation and activation has previously been shown to be regulated by SQLE in other cell types including hepatocellular carcinoma cells ( 109) and lung squamous cell carcinoma cells (110). In fact, SQLE-mediated cholesterol synthesis preserves breast cancer stem cell stemness through PI3K/AKT signaling, another proliferative survival pathway, upon stabilization of SQLE mRNA by long non-coding RNA 030 and poly(rC) binding protein 2 (111). Therefore, the metabolites produced by the action of SQLE may activate cell signaling pathways necessary for cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…A novel lnc030 was highly expression in breast cancer [66]. Inhibition of lnc030 expression by lentivirus-mediated short hairpins RNAs (shRNAs) reported markedly impaired colony formation and inhibited breast cancer initiation and progression, whereas ectopic lnc030 overexpression signi cantly increased colony formation and promoted initiation and progression of breast cancer [66]. These results demonstrated that lnc030 could act as a therapeutic target and biomarker in breast cancer.…”
Section: Therapeutic Use Of Lncrnas In Diseasesmentioning
confidence: 95%
“…Previous studies have demonstrated novel lncRNA biomarkers and identify therapeutic lncRNA targets [64,65]. A novel lnc030 was highly expression in breast cancer [66]. Inhibition of lnc030 expression by lentivirus-mediated short hairpins RNAs (shRNAs) reported markedly impaired colony formation and inhibited breast cancer initiation and progression, whereas ectopic lnc030 overexpression signi cantly increased colony formation and promoted initiation and progression of breast cancer [66].…”
Section: Therapeutic Use Of Lncrnas In Diseasesmentioning
confidence: 99%